Ground motion simulation of hypothetical earthquakes in the upper North Island of New Zealand. Issue 4 (2nd October 2021) - Dempsey, David; Eccles, Jennifer D.; Huang, Jonney; Jeong, Seokho; Nicolin, Elia; Stolte, Andrew; Wotherspoon, Liam; Bradley, Brendon A.
ABSTRACT: The upper North Island of New Zealand has large concentrations of population and infrastructure that make it vulnerable to earthquakes on the Kerepehi and Wairoa North faults. Using a physics-based simulator, we modelled 0–50 Hz ground motions for Mw 7.3 and Mw 6.6 characteristic earthquakes on these structures. We considered the effects of low-velocity basins beneath the Hauraki Rift and the city of Hamilton that can amplify ground shaking. For a Kerepehi Fault earthquake, long period (>1s) shaking was amplified a by factor of two to three in Hamilton and towns near the Firth of Thames. Severe to violent, long duration shaking would occur close to the source with the potential to trigger liquefaction that damages flood defence networks and farmland in the Hauraki Depression. Auckland, Hamilton and Tauranga could experience moderate to very strong shaking. Impacts in Auckland are larger for a Wairoa North Fault earthquake, which could generate peak ground accelerations of 0.5g at reservoir dams in the Hūnua Ranges, 0.2g at the international airport, and 0.1–0.2g at the CBD and port. Road, rail and transmission networks are vulnerable to disruption where they converge at infrastructure hotspots 10 km from the fault in South Auckland.